2002
DOI: 10.1037/1528-3542.2.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of normal aging and Alzheimer's disease on emotional memory.

Abstract: Recall is typically better for emotional than for neutral stimuli. This enhancement is believed to rely on limbic regions. Memory is also better for neutral stimuli embedded in an emotional context. The neural substrate supporting this effect has not been thoroughly investigated but may include frontal lobe, as well as limbic circuits. Alzheimer's disease (AD) results in atrophy of limbic structures, whereas normal aging relatively spares limbic regions but affects prefrontal areas. The authors hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
269
6
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(333 citation statements)
references
References 67 publications
40
269
6
10
Order By: Relevance
“…On the other hand, contrary to this hypothesis, there was no age by emotional valence interaction for item errors. Some previous studies exploring the positivity bias in LTM experiments also did not observe a differential positivity effect in elderly participants relative to young participants (Comblain, D"Argembeau, Van der Linden, & Aldenhoff, 2004;Denburg, Buchanan, Tranel, & Adolphs, 2003;Kensinger et al, 2002). It should be noted that the (lack of) age-related differences that was observed in this study is difficult to interpret because the two groups differed in terms of positive affect (as assessed by PANAS questionnaire), the young group rating higher on the positive dimension than the elderly group .…”
Section: < Insert Figure 2 About Here >mentioning
confidence: 81%
“…On the other hand, contrary to this hypothesis, there was no age by emotional valence interaction for item errors. Some previous studies exploring the positivity bias in LTM experiments also did not observe a differential positivity effect in elderly participants relative to young participants (Comblain, D"Argembeau, Van der Linden, & Aldenhoff, 2004;Denburg, Buchanan, Tranel, & Adolphs, 2003;Kensinger et al, 2002). It should be noted that the (lack of) age-related differences that was observed in this study is difficult to interpret because the two groups differed in terms of positive affect (as assessed by PANAS questionnaire), the young group rating higher on the positive dimension than the elderly group .…”
Section: < Insert Figure 2 About Here >mentioning
confidence: 81%
“…Consistent with this proposition, Carstensen and Turk-Charles (1994) found, in a study of prose recall, that although older adults remembered less neutral content than young adults, both age groups recalled equivalent amounts of emotional material. More recently, Kensinger, Brierley, Medford, Growdon, and Corkin (2002) also found that young and older adults showed similar memory enhancement effects for emotional words or pictures, as compared to neutral items. In addition, Davidson and Glisky (2002) found that memory for contextual information associated with important emotional news (flashbulb memories) was not affected by ageing.…”
Section: Identity But Not Expression 4 Identity But Not Expression Mementioning
confidence: 85%
“…Although limbic regions tend to be spared by increasing age (Kensinger, Brierley, Medford, Growdon & Corkin, 2002), changes in amygdalar function and connectivity are observed (St. Jacques, Dolcos & Cabeza, 2009), suggesting age-related differences in emotional processing. The amygdala comprises a series of subcortical nuclei in the medial-temporal lobe and is thought to exert a modulatory role on the hippocampus, which, in Cognitive Reserve and Positivity Effect 5 turn, enhances episodic memory performance for emotional stimuli (LaBar & Cabeza, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tests of executive functions (TMA & TMB) were administered as part of a neuropsychological test battery, at the end of which the test of emotional recall was also administered. The instructions for the emotional recall test were adapted from Kensinger et al (2002). At the beginning of the test, the experimenter informed the participants that they would be presented with a list of words, some of which would be negative, some would be positive and some would be neutral, and examples were given (e.g., "TABLE is neutral").…”
Section: Introductionmentioning
confidence: 99%